Diastereoselective [3 + 3] cycloaddition reaction of 2-arylideneindan-1, 3-diones with β-naphthols: Efficient assemble of immunosuppressive pentacyclic chromanes. Issue 10 (5th March 2020) - Li, Na; Tu, Liang; Cheng, Guiguang; Sa, Houling; Li, Zhenghui; Feng, Tao; Zheng, Yongsheng; Liu, Jikai
Graphical abstract: Highlights: Formal [3 + 2] cycloadddition of 2-arylideneindan-1, 3-diones with β-naphthols. Highly efficient, mild approach for the construction of pentacyclic chromanes. Broad substrates scope and easily derivation. Successful demonstration of gram scale synthesis. Promising immunosuppressive activity. Abstract: A base promoted diastereoselective formal [3 + 3] cycloaddition reaction of 2-arylideneindan-1, 3-diones with β-naphthols towards the synthesis of functionalized pentacyclic indeno[1, 2- b ]chromen-(4b H )-ones has been developed. This methodology is appreciated in terms of diastereoselectivity and mild conditions. In addition, the immunosuppressive assay indicates that one of the products has selective inhibition on T -cell proliferation (IC50 value of 8.73 μM).